Peranan Perencanaan Bagi Pengembangan Masjid Raya Nurul Hidayah Kebayoran Lama Jakarta Selatan - Pachad Pachad; Sobirin Sobirin (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
The Great Mosque of Nurul Hidaya Kebayoran Lama, South Jakarta, is used as the center of local Muslim activities. Today the function of the mosque as a place to accommodate various religious activities and not just a place for ritual worship. This study uses descriptive qualitative research. The results of this study indicate that the role of planning for the development of the Nurul Hidayah Great Mosque includes several steps in compiling an activity program aimed at smoothing all existing activities, program of activities, consists of 10 to 25 years long term planning programs, 7 to 5 years medium term, and a year of short term planning program.Keywords: the role of planning for mosque development AbstrakMasjid Raya Nurul Hidayah Kebayoran Lama Jakarta Selatan dijadikan sebagai pusat kegiatan kaum muslimin setempat. Dewasa ini fungsi masjid sebagai wadah untuk menampung berbagai kegiatan keagamaan dan bukan hanya tempat untuk ibadah ritual saja. Penelitian ini menggunakan penelitian deskriptif kualitatif. Hasil penelitian ini menunjukkan bahwa Peranan perencanaan bagi Pengembangan Masjid Raya Nurul Hidayah mencakup beberapa langkah dalam menyusun program kegiatan yang bertujuan melancarkan semua kegiatan yang ada, program kegiatan yaitu perencanaan jangka panjang 10 sampai 25 tahun, perencanaan jangka menegah yaitu 7 sampai 5 tahun dan perencanaan jangka pendek selama 1 tahun.Kata Kunci: Peranan Perencanaan Pengembangan Masjid